High Dielectric Breakdown Strength Nanoplatelet‐Based Multilayer Thin Films - Bethany Palen; Ethan T. Iverson; Matthew G. Rabaey; Shaik Merkatur Hakim Marjuban; Carolyn T. Long; Thomas J. Kolibaba; Annie Benson; Homero Castaneda‐Lopez; Jaime C. Grunlan (Macromolecular Materials and Engineering, 2023)
Abstract Dielectric materials that can withstand high voltages are of great interest due to the growing need for high‐performance insulation systems in electronics. Polymer nanocomposites have gained popularity as electrical insulators due to their processability, high operating voltage, and tortuous paths for current flow created by the nanoparticles in the polymer matrix. The dielectric breakdown strength of a relatively thick multilayer thin film containing polyethylenimine (PEI) and vermiculite clay (VMT), thickened with tris(hydroxymethyl)aminomethane (tris), is evaluated as a function of bilayers (BL) deposited. The resulting nanobrick wall structure of this clay‐based assembly is ideal for protective insulation. An 8 BL PEI+tris/VMT film achieves a dielectric breakdown strength of 245 kV mm−1, with a thickness of 5 µm. With increasing bilayers, the breakdown strength gradually decreases, but 20 BL of PEI+tris/VMT achieves a breakdown voltage of 2.36 kV. This nanoplatelet‐based system is the first “thick growing” layer‐by‐layer deposited film to be used as an insulating layer. Its unusually high breakdown strength can be useful for the protection of various high voltage electronics.